PETROGENESIS OF THE OPHIOLITIC GIANT CHROMITE DEPOSITS OF KEMPIRSAI, KAZAKHSTAN: A STUDY OF SOLID AND FLUID INCLUSIONS IN CHROMITE - Melcher F.; Grum W.; Simon G.; Thalhammer T.V.; Stumpfl E.F. (My University, 1997)
Chromites forming giant orebodies in the souther part of the Early Palaeozoic ophiolite sequence of the the Kempirsai Massif (Kazakhstan, Urals) contain a large number of inclusions, i.e. silicates, sulphides, alloys, arsenides, and fluids. The chromite orebodies ale surrounded by dunite envelopes of variable thickness, which show, transitional boundaries to harzburgite host rocks. The composition of ore-forming chromites in depleted mantle rocks of the southern part of the the massif (Main Ore Field) is rather uniform, shozwing high cr-number [100Cr/(Cr+Al), 78-84] and mg-number [100Mg/(Mg+Fe2+), 51-85] values. Smaller bodies of Al-rich spinel in the northern and western part of the massif (Batamshinsk) have variable cr-number (38-60) and mg-number (50-88) values. Three textural types of inclusions in chromite are distinguished: (1) In Main Ore Field chromites, primary silicate inclusions generally have high mg-number (>95), Cr and Ni, and ale dominated by pargasitic amphibole, forsterite, diopside, enstatite and Na-phlogopite. Chromite formed over a temperature range from similar to 1200 degrees to <1000 degrees C at oxygen fugacities 1-2 log units above the fayalite-magnetite-quartz (FMQ) buffer. A diversity of primary and secondary platinum-group minerals (PGM) is described from the chromitites, including alloys, sulphides, sulpharsenides and arsenides Of Ru, Os, Ir, Rh, Ni, Cu, Fe and Co. Alloys, sulphides and arsenides free of platinum-group elements are attributed to serpentinization of chromitite. (2) In addition to primary PGM and hydrous silicates, fluid inclusions of up to 50 mu m size are frequency included in chromite within chromite-amphibole veins discordant to massive chromitite in the Main Ore Field. The fluids are low to moderately saline, sodium-dominated aqueous solutions with complex gas contents. Variable amounts of water, hydrogen, hydrocarbons, carbon dioxide and nitrogen have been determined in inclusion-rich samples. (3) In the northern and western part of the Kempirsai massif; complex silicate-oxide assemblages formed in small orebodies of orbicular ill-rich chrome spinel. Chlorite, amphibole, hydrogarnet, sphene, manganoan ilmenite and Ca-Ti oxide are documented in addition to Ni sulphides and rare PGI. The formation of chromitite in the Kempirsai Massif is explained in terms of a multi-stage process involving mantle fluids. Low-Cr, high-ill spinel present in small orebodies in the northern and western part of the massif formed from mid-ocean ridge basalt (MORB)-type melts extracted from fertile mantle in an extensional tectonic setting. The large orebodies and the amphibole-chromite veins in the southern pal formed later from interaction of hydrous, second stage high-Mg melts and fluids with depleted mantle in a convergent tectonic setting Metasomatic alteration of the mantle wedge above subducted dust by fluids played an important role in generating second-stage melts and in releasing metals.
Keywords: Palaeozoic; Paleozoic; Палеозой